2016
DOI: 10.1016/j.antiviral.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

An influenza A virus (H7N9) anti-neuraminidase monoclonal antibody with prophylactic and therapeutic activity in vivo

Abstract: Zoonotic A(H7N9) avian influenza viruses emerged in China in 2013 and continue to be a threat to human public health, having infected over 800 individuals with a mortality rate approaching 40%. Treatment options for people infected with A(H7N9) include the use of neuraminidase (NA) inhibitors. However, like other influenza viruses, A(H7N9) can become resistant to these drugs. The use of monoclonal antibodies is a rapidly developing strategy for controlling influenza virus infection. Here we generated a murine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 47 publications
1
47
0
Order By: Relevance
“…It is interesting that MAbs which bind to the HB region, e.g., 1E8 and 10F4, did not block virus infection, implying that the HB site is not required for virus entry. Our data and the findings of Wilson et al (21) indicate that MAbs to the HB site can protect mice from lethal A(H7N9) virus challenge, and for this reason the HB site may be an attractive target for antibodies selected for development as antivirals.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…It is interesting that MAbs which bind to the HB region, e.g., 1E8 and 10F4, did not block virus infection, implying that the HB site is not required for virus entry. Our data and the findings of Wilson et al (21) indicate that MAbs to the HB site can protect mice from lethal A(H7N9) virus challenge, and for this reason the HB site may be an attractive target for antibodies selected for development as antivirals.…”
Section: Discussionsupporting
confidence: 72%
“…Escape mutant selection and site mutagenesis in our study identified residues 368, 370, 371, 373, 400, and 434 as critical contacts for MAbs 1E8, 5H11, 7F12, and 10F4. These amino acids are also within defined epitopes recognized by G70C NA-specific MAbs (17,20,21,40). Amino acid 345 appears to be relatively distant from other identified amino acids but was selected by MAb 5H11, which also selected the K434E escape mutant, suggesting that the footprint of 5H11 covers this entire area.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Patients were characterized by rapidly progressive pneumonia, respiratory failure, acute respiratory distress syndrome and even with 35% fatality rate [2][3][4]. It has caused serious concerns for public health throughout the world.…”
Section: Introductionmentioning
confidence: 99%
“…The antihemagglutinin (anti-HA) antibodies play a dominant role in protection against HA-matched influenza virus, while anti-NA antibodies may also be protective in the case of mismatched HA (10)(11)(12)(13)(14)(15)(16). HA antibodies block viral attachment to the target cell surface, and if the virus enters into the endolysosome, these antibodies also block viral uncoating and release of the nucleoprotein into cytoplasm.…”
mentioning
confidence: 99%